Information-Centric Networking in next-generation communications scenarios. (15th February 2017) - Morelli, Alessandro; Tortonesi, Mauro; Stefanelli, Cesare; Suri, Niranjan
Abstract: Next-generation networking environments, characterized by the overlapping of wireless networks of different types, are emerging as a new and extremely interesting scenario. Their high dynamicity and heterogeneity present significant challenges from the communications perspective, which call for the adoption of new paradigms based on opportunistic and Information-Centric Networking (ICN) approaches. Applications operating in next-generation environments have peculiar characteristics that could benefit from ICN-based middleware solutions. This paper presents ICeDiM, a middleware we designed for ICN communications in next-generation scenarios, which builds on top of the innovative concept of Application-level Dissemination Channels (ADCs) with tunable permeability levels. A thorough and in-depth experimental evaluation of ICeDiM in a next-generation environment realistically simulated using ICeONE, a modified version of the well-known ONE simulator, demonstrates that our approach can achieve very good performance levels in terms of delivery ratio and network resource consumption.